Health status of male steel workers at an electric arc furnace (EAF) in Trentino, Italy. Issue 1 (December 2016) - Cappelletti, Roberto; Ceppi, Marcello; Claudatus, Justina; Gennaro, Valerio
Abstract Background The aim of this retrospective cohort study was to determine if the workers of an Electric Arc Furnace (EAF), which recycles scrap, had higher mortality and morbidity due to possible exposure to pollutants at work. EAFs do not run on coke ovens. In EAFs 40 % of the particulate matter (PM) is made up of PM2.5 . The foundry dust contained iron, aluminum, zinc, manganese, lead, chromium, nickel, cadmium, mercury, arsenic, polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls and dioxins. Methods Mortality study : a cohort of 331 exposed workers (6731 person-years) was studied from 19/03/1979 to 31/12/2009 (mean follow up 20.7 years). The group of exposed workers was compared to the general population and to a small control group of 32 workers from the same company. Morbidity study : rates of exemption from health fee for the seven major diseases of 235 exposed workers were compared to the rates of exemption in the Province of Trento. Results Mortality study : an excess mortality was found in the exposed workers as compared to thegeneral population (SMR 1.13; 95 % CI: 0.76–1.62; 29 deaths) and to theinternal group (RR 2.34; 95 % CI: 0.39–95.7). The mortality rate was increased forall tumours (SMR 1.36; 95 % CI: 0.75–2.29; 14 cases), for lung cancer (SMR 3.35; 95 % CI 1.45–6.60; 8 cases), forischemic heart disease (SMR 1.27; 95 % CI: 0.35–3.26; 4 cases), forchronic liver disease (SMR 1.16; 95 % CI: 0.14–4.20; 2 cases) and forinjury and poisoning (SMR 1.32; 95 % CI: 0.48–2.88; 6 cases). Morbidity study : there was a statistically significant increase of diabetes, rheumatoid arthritis, hypertension and cardiovascular diseases in exposed workers. Conclusions With the limitations of this relatively small cohort, we found a statistically significant increase of diabetes, cardiovascular diseases and deaths due to lung cancer in exposed workers. These findings cannot be explained by PAH exposure alone; metal particulates are the most important pollutants in the working area of EAFs. A reliable method for measuring metal PM in tissues is urgently needed for exposure assessment. This study underlines the necessity to maximize the standards of security towardfoundry dusts/diffuse emission. Further studies on EAF's are needed to confirm our findings and to increase statistical power.